Mucosal-Associated Invariant T Cells Are Depleted and Exhibit Altered Chemokine Receptor Expression and Elevated Granulocyte Macrophage-Colony Stimulating Factor Production During End-Stage Renal Disease - Juno, Jennifer A.; Waruk, Jillian L. M.; Wragg, Kathleen M.; Mesa, Christine; Lopez, Carmen; Bueti, Joe; Kent, Stephen J.; Ball, T. Blake; Kiazyk, Sandra A. (Frontiers in Immunology, 2018)
Background: End stage renal disease (ESRD) is associated with an increased susceptibility to infectious diseases, including infection with Mycobacterium tuberculosis (Mtb). Mucosal associated invariant T (MAIT) cells recognize vitamin B metabolites produced by many bacterial species, including Mtb, and may play an important role in providing protective immunity against tuberculosis infection in the lung. To date, little is known about MAIT cell frequency, phenotype or function in ESRD patients. Methods: MAIT cells, identified by surface marker expression or MR1 tetramer binding, were characterized in 20 ESRD and 20 healthy control participants by multicolour flow cytometry. Ex vivo MAIT cell phenotype and cytokine production following PMA/ionomycin, IL-12/IL-18 or E. coli stimulation were determined. Monocyte phenotype and plasma CRP/inflammatory cytokine levels were quantified by flow cytometry, ELISA and multiplex bead array. Results: Peripheral blood MAIT cells were significantly depleted among ESRD patients compared to controls by both phenotypic and tetramer analysis, and exhibited a loss of CXCR3 expression coupled to increased expression of CCR6 and CXCR6. ESRD was also associated with a shift in MAIT PMA-induced cytokine production away from IFN production and toward GM-CSF secretion, and a loss of E. coli-stimulated TNF expression. Loss of IFN expression was associated with a combination of age, alterations in Tbet and Eomes expression, and inflammatory plasma cytokine levels. Conclusions: The loss of peripheral blood MAIT cells and associated shifts in tissue homing receptor expression and GM-CSF production may contribute to an immune environment that is permissive to bacterial replication, particularly in the lungs.